The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/molbev/msn116
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Ultraconservation Divergence in Primates

Abstract: The distribution and evolution of ultraconserved elements (UCEs, DNA stretches that are perfectly identical in primates and rodents) were examined in genomes of 3 primate species (human, chimpanzee, and rhesus macaque). It was found that the number of UCEs has decreased throughout primate evolution. At least 26% of ancestral UCEs have diverged in hominoids, whereas an additional 17% have accumulated one or more single nucleotide polymorphisms in the human genome. Sequence polymorphism analyses indicate that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Although further study is required to explain the immutability of UCEs after lineage divergence and sequence fixation across a long evolutionary history, we cannot rule out this possibility. It also should be noted that the absence of UCRs in species from the same lineage does not necessarily mean that those UCRs disappeared in those species but rather that they may exist as derivative sequences by mutation [2,15,28,29]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although further study is required to explain the immutability of UCEs after lineage divergence and sequence fixation across a long evolutionary history, we cannot rule out this possibility. It also should be noted that the absence of UCRs in species from the same lineage does not necessarily mean that those UCRs disappeared in those species but rather that they may exist as derivative sequences by mutation [2,15,28,29]. …”
Section: Resultsmentioning
confidence: 99%
“…Large numbers of DNA elements (≥200 bp) exhibiting 100% similarity have been found to be conserved across several mammalian species [1,2]. Shorter ultraconserved elements (UCEs) longer than 50 bp and 100 bp have also been identified in several insect species and plants, respectively [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we found that similarly to the GC content and divergence, the SNP density in HCTs is roughly constant throughout the HCT, but is strikingly different from the flanking sequences. For example, the overall SNP density in HCTs for E2F1 (0.2 SNPs/kb) is comparable to the SNP density in ultraconserved regions in the human genome (Ovcharenko 2008). This value is fivefold lower than that observed in flanking sequences (Fig.…”
Section: Tfbss In Conserved Hcts Evolve Under Purifying Selectionmentioning
confidence: 94%
“…This rapid burst of base pair substitutions in HAR1 was interpreted as evidence that HAR1 acquired an important new function in humans and in particular may have altered human brain by influencing the activity of a whole network of genes (Pollard et al 2006a). On the other hand, many highly conserved noncoding sequences have been found (Dermitzakis et al 2002;Bejerano et al 2004Bejerano et al , 2006Ovcharenko 2008;Stephen et al 2009).…”
Section: Introductionmentioning
confidence: 99%